9x+27-6x+12=60

Simple and best practice solution for 9x+27-6x+12=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+27-6x+12=60 equation:


Simplifying
9x + 27 + -6x + 12 = 60

Reorder the terms:
27 + 12 + 9x + -6x = 60

Combine like terms: 27 + 12 = 39
39 + 9x + -6x = 60

Combine like terms: 9x + -6x = 3x
39 + 3x = 60

Solving
39 + 3x = 60

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-39' to each side of the equation.
39 + -39 + 3x = 60 + -39

Combine like terms: 39 + -39 = 0
0 + 3x = 60 + -39
3x = 60 + -39

Combine like terms: 60 + -39 = 21
3x = 21

Divide each side by '3'.
x = 7

Simplifying
x = 7

See similar equations:

| 6x+5=6x+21 | | -2x-10=6x+14 | | 1/3(4x+2)=2(3-4x)+4 | | 8x+30=5x+105 | | -0.03x=1.72x+1.75 | | 5=-1/2(2X-4)-2X | | 5x+14+x=3x-7 | | 8x+7=8(x-1) | | -6x-12=3x+15 | | 6(x-7)=3x | | x+7/8=2x-7/8 | | n(n+3)=2n+1 | | 3/2(3x+3)=2(1-3x)+13 | | 3x+22=3+6x-5 | | 4(5+x)=20 | | 7(a+b)=7a | | 3(2x+9)=6x | | 90z+10z=100 | | 5a+10a=20 | | 1y+1=x | | 2x^3-x^2-20x+10=0 | | 10x+13=6x+113 | | 66-3x=15x+22 | | x*x+3=28 | | 97-3x=33x+17 | | 18P-0= | | 134-10x=9x+18 | | 4x=36+3x | | -66.66y=22 | | 22=15x | | 25-5= | | -0.003x^2+0.577x+2=0 |

Equations solver categories